Crowdsourcing Practices in Academic Libraries in Nigeria - Opele, Jacob Kehinde; Daramola, Cecilia Funmilayo; Onoyeyan, Glory O. (Evidence Based Library and Information Practice, 2025)
Objective – In this study, we investigated the utilization of crowdsourcing practices among academic librarians in Nigeria, encompassing all 36 states across the 6 geopolitical zones of the country.Methods – We employed the descriptive survey design. The target population consisted of academic librarians who were members of the national professional online group of the association known as the NLA where scholars shared professional thoughts and advancements.Results – The findings revealed a high level of awareness about crowdsourcing among academic librarians, with their experiences spanning various areas such as knowledge discovery and management (RII = 0.76), broadcast search (RII = 0.63), the distribution of human intelligence tasking (RII = 0.62), and peer-vetted creative production (RII = 0.59). In terms of the extent of practice, electronic document exchange services received the highest relative importance index score (RII = 0.73), followed closely by e-payment platforms (RII = 0.73). The findings also indicated that crowdsourcing is considered beneficial for collection development (RII = 0.68) and is perceived to be useful in the procurement of new items for the library (RII = 0.67). However, the study identified inadequate institutional support (RII = 0.91) as the foremost challenge impeding the adoption and implementation of crowdsourcing practices in academic libraries in Nigeria. Other challenges included inadequate electricity supply and unstable Internet network systems in Nigeria which has hindered full deployment of crowdsourcing in academic library settings in the country.Conclusion – This study emphasized the importance of the adoption and implementation of crowdsourcing practices in academic libraries in Nigeria. Addressing challenges related to institutional support, electricity supply, and Internet connectivity is crucial to creating an enabling environment for successful crowdsourcing initiatives.